Organo-Mineral Fertilizer Improves Ocimum basilicum Yield and Essential Oil - Roberta Camargos de Oliveira; Mércia Freitas Alves; José Magno Queiroz Luz; Arie Fitzgerald Blank; Daniela Aparecida de Castro Nizio; Paulo César de Lima Nogueira; Sérgio Macedo Silva; Renata Castoldi (Plants)
The production of Ocimum basilicum (basil) crop depends upon the availability of all nutrients in the soil solution. There is a lack of information about its performance, at tropical conditions, using new fertilizer formulations, such as organo-mineral fertilizers, mainly under protected cultivation. These types of fertilizers combine benefits of the main fertilizers used in agriculture (organic and chemical). Therefore, organo-mineral fertilizers enhance soil health, provide a balanced nutrient supply, improve crop yields and quality. and promote environmental sustainability, making them a cost-effective and eco-friendly solution for sustainable crop production. This work aimed to evaluate the biomass and essential oil of basil varieties, with organo-mineral fertilization in different agricultural systems. Each experiment was conducted in a randomized block design, with three replications in a 2 × 4 factorial scheme, being two varieties of basil (“Sweet Dani” and “Cinnamon”) and four fertilizers: organo-mineral source, mineral source, organic source and the natural fertility of the soil. The evaluated characteristics were plant height, fresh biomass of plants, content, yield and the chemical composition of the essential oil. The organo-mineral sources of fertilizer provide better values for fresh biomass (average of 1175.90 and 1032.83 g per plant via greenhouse cultivation and field cultivation, respectively), essential oil yield (14.57 and 11.89 g per plant via greenhouse cultivation and field cultivation, respectively) and the dominant compounds for both cultivars of O. basilicum. Protected cultivation is the better environmental condition for obtaining the highest performance of O. basilicum cultivars about biomass and essential oil. The content of essential oil is not affected by the agricultural systems (greenhouse and field). The major compounds of essential oil under Brazilian crop conditions are Linalol and (E)-mehyl cinnamate in “Cinnamon” and neral and geranial (citral) in “Sweet Dani”.